Implementing for Results : Program Analysis of the HIV/STI Interventions for Sex Workers in Benin - Semini, Iris; Batona, Georges; Lafrance, Christian; Kessou, Léon; Gbedji, Eugène; Anani, Hubert; Alary, Michel (Taylor and Francis, 2013)
HIV response has entered a new era shaped by evidence that the combination of interventions impacts the trajectory of the epidemic. Even proven interventions, however, can be ineffective if not to scale, appropriately implemented, and with the right combination. Benin is among the pioneering countries that prioritized HIV prevention for sex workers and clients early on. Effective implementation up to 2006 resulted in consistent condom use among sex workers increasing from 39% to 86.2% and a decline in prevalence of gonorrhea from 5.4% to 1.6%. This study responds to the growing concern that, although proven interventions for female sex workers (FSWs) were expanded in Benin since 2008, indicators of coverage and behaviors are far from satisfactory. The quest to better understand implementation and how to render service delivery efficient and effective resonates with increased emphasis in the international arena on return for investments. Quantitative and qualitative methods were utilized to collect data. The output measured is the number of sex workers seeking Sexually Transmitted Infection (STI) care at user-friendly STI Clinics (SCs). Data were collected for 2010–2011 in nine regions of Benin. While recognizing that commitment to scale up is commendable, the study revealed deficiencies in program design and implementation that undermine outcomes. The selected mix of interventions is not optimal. Allocation of funds is not proportionate to the needs of FSW across regions. Only 5 of 41 SCs were fully functional at time of study. Free distribution of condoms covers only 10% of needs of FSWs. Funding and financing gaps resulted in extended interruptions of services. Successful HIV prevention in Benin will depend on the effective and efficient implementation of well-funded programs in sex work setting. Resources should be aligned to local sex work typology and presence in communities. A national framework defining an appropriate mix of interventions, management structure, referral mechanisms, and operational standards is required to guide rigorous implementation. Health services, in particular functional and user-friendly SCs coupled with mechanisms that link community-based work and health facilities should be strengthened to ensure STI care/anti-retroviral treatment expansion. Without leadership of sex workers, any attempt to end HIV will be unsuccessful.